Hydration and fluid replacement knowledge, attitudes and behaviours of Gaelic football players - Ní Chéilleachair, N.; Skelly, F.; O Catháin, C.; O Neill, C. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Euhydration is required for optimal health and sporting performance. Significant dehydration has been associated with impaired cognitive function and sporting performance and an increased perception of effort. Invasion team sports, such as Gaelic football, are characterised by intermittent high-intensity bouts of activity over a prolonged period and have been associated with potentially high sweat rates. Given the physically demanding nature of Gaelic football training and competition, adequate fluid intake is essential for optimal health and performance. Therefore the aim of this study was to investigate hydration and fluid replacement knowledge, attitudes and behaviours of Gaelic football players.